Evaluation of Hospital Readiness and Strategic Planning in Implementing the Priority Cancer Service Mentorship Program (Qualitative Study at Anutapura Hospital, Palu, and Torabelo Hospital, Sigi) - Zakiyatun Murtafi'ah Hamzah; Rian Andriani; Yani Restiani Widjaja (Sean Institute, 2026)
Cancer is one of the catastrophic diseases that requires high treatment costs, long-term care, and poses a significant burden on the health system. In Indonesia, there are 514 hospitals stratified according to their expected capacity to provide cancer services; however, assessments in Central Sulawesi Province revealed that network hospitals remain at the basic level. This phenomenon highlights a gap between the growing need for cancer services and the actual capacity of hospitals. This study aims to evaluate the readiness of available resources and to analyze the strategic planning of hospitals in supporting the implementation of priority cancer service programs. A qualitative method with a case study design was applied, using interviews, observations, and document reviews. Data were analyzed through the stages of data reduction, data display, and conclusion drawing. The findings indicate that Anutapura Palu Hospital has reached an intermediate level with better readiness in terms of input, process, and product, while Torabelo Sigi Hospital remains at the basic level with significant limitations in human resources, facilities, operational documents, and funding. Strategic planning at Anutapura Palu Hospital has been more adaptive, enabling faster operationalization of cancer services, while Torabelo Sigi Hospital requires acceleration in governance documents, infrastructure development, and technical assistance. This study emphasizes that the success of cancer service implementation is highly determined by input readiness, process effectiveness, product outcomes, and adaptive strategic planning.